Internet governance : infrastructure and institutions - Bygrave, Lee A.; Bing, Jon, 1944- (Oxford : Oxford University Press, 2009)
The significance of the governance of the Internet is increasing and the issue has become the subject of growing public and media interest. This book takes a detailed, systematic, and non-polemical look at the issue.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Internet -- Law and legislation; Internet -- Management -- International cooperation